Cultures in conflict : a documentary history of the Mormon War in Illinois - Hallwas, John E.; Launius, Roger D. (Logan : Utah State University Press, 1995)
Cultures in Conflict offers students of history an invaluable source of documents regarding the history of the Mormon presence in Illinois. Few local histories are so academically sound.-Illinois TimesHallwas and Launius have compiled and written the most balanced and thorough account yet of the events and circumstances that led to the forced Mormon exodus from Nauvoo following the mini civil war that erupted in Illinois during the 1849s.
The coming of the Mormons -- Origins of the conflict -- The trouble in Nauvoo -- The murders in Carthage -- The trial and the violence -- The exodus and the battle of Nauvoo.
Includes bibliographical references (pages 351-353) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
JSTOR
Keywords: Latter Day Saints -- Illinois -- History -- 19th century -- Sources; Illinois -- History -- 1778-1865 -- Sources; Nauvoo (Ill.) -- History -- Sources; Mormons -- Illinois -- Histoire -- 19e siècle -- Sources; Illinois -- Histoire -- 1778-1865 -- Sources; HISTORY -- State & Local; HISTORY -- State & Local -- General; HISTORY -- United States -- 19th Century; Mormons; Illinois; Illinois -- Nauvoo; 1778-1899; History; Sources